Barriers to Sustaining Dog Vaccination Campaigns against Rabies: Perspectives from Dog and Cat Owners and Other Stakeholders in Kisarawe District, Tanzania (Tanzania Medical Journal, 2025)
BackgroundRabies is caused by a neurotropic virus of the genus Lyssavirus of the family Rhabdoviridae, that affects all mammals. About 99% of the transmission of the virus to humans are due to bites from domestic dogs. Rabies is a neglected tropical disease that causes more than 59,000 human deaths each year in the world, particularly in Asia and Africa. It causes a loss of 3.7 million Disability Adjusted Years per year and about 8.6 billion USD of economic losses. Over 80% of susceptible dog populations remain unvaccinated in Africa, and as a result, rabies remains endemic in the continent. Dog vaccination, provision of post-exposure prophylaxis to people bitten by dogs and awareness are the major interventions to prevent and control rabies. Kisarawe district in Tanzania is considered to be among the hotspots for rabies as it borders the Nyerere National Park. Despite this fact, rabies vaccination coverage of dogs in Kisarawe remains low.ObjectiveTo explore barriers to sustaining dog vaccination campaigns against rabies in Kisarawe district, Tanzania.MethodsThis was an exploratory qualitative research design which was conducted in Kisarawe District, Pwani Region in Tanzania. A total of thirty-three in-depth interviews were administered to dog owners, cat owners, livestock officers and clinicians. Data were summarized and analyzed using a thematic approach, systematic coding and with the aid of NVivo v14 software for qualitative analysis.ResultsSix themes emerged that reflect perceptions of respondents: “Awareness on rabies disease”; “Prevention of rabies including post-exposure prophylaxis of a person bitten by rabid dog”; “Reasons for dog owners not to bring dogs for vaccination during the campaigns and Low turn up among dog/cat owners to vaccinate their dogs”, “inadequate knowledge among dog and cat owners on rabies protection by the vaccine”; “misconception that vaccine can do harm to dogs and cats; and “challenges facing livestock officers to vaccinate dogs”. Specific barriers include shortage of field staff, equipment and anti-rabies vaccines. In addition, low turn up among dog/cat owners to vaccinate their dogs during campaigns was a big barrier.ConclusionThe study findings have revealed barriers to achieving high coverage of dog vaccination despite presence of vaccination campaigns in Kisarawe district. Education and awareness on dog and cat owners on vaccination against rabies should be conducted frequently while implementing a scheduled provision of free rabies vaccine. Vaccines, supplies, and related equipment should be always available and distributed for increased vaccination coverage.